A Stereoselective [3+1] Ring Expansion for the Synthesis of Highly Substituted Methylene Azetidines. (1st September 2017) - Schmid, Steven C.; Guzei, Ilia A.; Schomaker, Jennifer M.
Abstract: The reaction of rhodium‐bound carbenes with strained bicyclic methylene aziridines results in a formal [3+1] ring expansion to yield highly substituted methylene azetidines with excellent regio‐ and stereoselectivity. The reaction appears to proceed through an ylide‐type mechanism, where the unique strain and structure of the methylene aziridine promotes a ring‐opening/ring‐closing cascade that efficiently transfers chirality from substrate to product. The resultant products can be elaborated into new azetidine scaffolds containing vicinal tertiary‐quaternary and even quaternary‐quaternary stereocenters.